Evaluating tooth strontium and barium as indicators of weaning age in Pacific walruses. Issue 12 (28th September 2020) - Clark, Casey T.; Horstmann, Lara; Misarti, Nicole
Abstract: Lactation length and weaning age provide important information about maternal investment, which can reflect the health and nutritional status of the mother, as well as broader reproductive strategies in mammals. Calcium‐normalized strontium (Sr) and barium (Ba) concentrations in the growth layers of mammalian teeth differ for nursing animals and those consuming non‐milk foods, thus can be used to estimate age‐at‐weaning. To date, this approach has been used only for terrestrial animals, and almost exclusively for primates. The goal of this study was to determine whether Sr and Ba concentrations in the cementum of Pacific walrus Odobenus rosmarus divergens teeth can be used to estimate weaning age. Teeth from 107 walruses were analysed using laser ablation inductively coupled plasma mass spectrometry, and calcium‐normalized 88 Sr and 137 Ba concentrations were quantified. For most walruses, both Sr and Ba concentrations exhibited rapid changes in early life. Ba concentrations matched closely with expected patterns in the published literature, rapidly declining from high to low concentrations (typically from 10 ppm to 5 ppm). In contrast, Sr exhibited a pattern opposite to that presented in studies of terrestrial mammals, appearing nearly identical to Ba (typically declining from 400 ppm to 200 ppm). To explain these findings, we present conceptual models of the factors generating weaning signals in Sr and Ba for terrestrial mammals, as well as a new, hypothetical model for walruses. Both a visual and mathematical approach to weaning age estimation indicated a median weaning age of walruses at the end of the second year of life (in the second dark layer of the tooth cementum), with many walruses estimated to have weaned in their third year of life, and a smaller group weaning in their fourth or fifth year. This is later than expected, given a published estimate of walrus weaning at 18–24 months. These results do not conclusively support the use of tooth Sr and Ba for estimating weaning age in walruses, and further research is warranted to better understand the drivers of the observed patterns of Ba and Sr accumulation in walrus teeth.